Chitinase mRNA Levels Determined by QPCR in Crab-Eating Monkey (Macaca fascicularis) Tissues: Species-Specific Expression of Acidic Mammalian Chitinase and Chitotriosidase - Uehara, Maiko; Tabata, Eri; Ishii, Kazuhiro; Sawa, Akira; Ohno, Misa; Sakaguchi, Masayoshi; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (Genes, 2018)
Mice and humans express two active chitinases: acidic mammalian chitinase (AMCase) and chitotriosidase (CHIT1). Both chitinases are thought to play important roles in specific pathophysiological conditions. The crab-eating monkey (Macaca fascicularis) is one of the most frequently used nonhuman primate models in basic and applied biomedical research. Here, we performed gene expression analysis of two chitinases in normal crab-eating monkey tissues by way of quantitative real-time polymerase chain reaction (qPCR) using a single standard DNA molecule. Levels of AMCase and CHIT1 messenger RNAs (mRNAs) were highest in the stomach and the lung, respectively, when compared to other tissues. Comparative gene expression analysis of mouse, monkey, and human using monkey⁻mouse⁻human hybrid standard DNA showed that the AMCase mRNA levels were exceptionally high in mouse and monkey stomachs while very low in the human stomach. As for the CHIT1 mRNA, we detected higher levels in the monkey lung when compared with those of mouse and human. The differences of mRNA expression between the species in the stomach tissues were basically reflecting the levels of the chitinolytic activities. These results indicate that gene expression of AMCase and CHIT1 differs between mammalian species and requiring special attention in handling data in chitinase-related studies in particular organisms.
Keywords: species-specific gene expression; chitinolytic activity; crab-eating monkey; nonhuman primate model; human; acidic mammalian chitinase; mouse; chitotriosidase; asthma; qPCR